PROBLEM-BASED LEARNING-BASED CIVICS E-MODULE DEVELOPMENT TO INCREASE UNDERSTANDING OF PANCASILA VALUES MATERIALS GRADE V - Endang Suhartami; Ani Nur Aeni; Dety Amelia Karlina (Universitas Majalengka, 2023)
The lack of development of teaching materials in learning activities impacts student understanding because students cannot fully explore their knowledge. As a result, students feel bored because there are no other teaching materials that can be a source of student learning at school where the teacher cannot provide the teaching materials needed by students, so these conditions become a factor in conducting this research. This study uses the Research and Development methodology with the ADDIE product development model, which consists of five phases: analysis, design, development, implementation, and evaluation. Data collection methods include observation, interviews, and questionnaires. The data analysis method used in this research is descriptive qualitative and quantitative analysis. This study aimed to determine the feasibility of problem-based PPKn E-Module development on understanding Pancasila values and the effectiveness of problem-based PPKn E-Module implementation in increasing student understanding. Based on research conducted by researchers on the development of E-Modules, the results show that E-Modules are suitable for use in learning with a feasibility level obtained from media experts of 95%, material experts of 92.5%, individual student trials of 89.1%, small group trials of 83%, and field trials of 86.5%. Data analysis from the students' pre-test and post-test showed a difference in average results between the pre-test of 71.61% and the post-test of 83.39, so it can be said that problem-based learning-based PPKn E-Module is effectively used in learning. Minimnya pengembangan bahan ajar dalam kegiatan pembelajaran memberikan dampak terhadap tingkat pemahaman siswa karena siswa tidak bisa menggali pengetahuannya dengan maksimal. Akibatnya siswa merasa bosan karena tidak adanya bahan ajar lain yang dapat menjadi sumber belajar siswa di sekolah yang mana guru tidak mampu menyediakan bahan ajar yang diperlukan siswa sehingga kondisi tersebut menjadi faktor dilakukannya penelitian ini. Penelitian ini menggunakan metodologi Research and Development dengan model pengembangan produk ADDIE, yang terdiri dari lima fase: analisis, desain, pengembangan, implementasi, dan evaluasi. Metode pengumpulan data meliputi observasi, wawancara, dan kuesioner. Metode analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif kualitatif dan kuantitatif. Tujuan penelitian ini untuk mengetahui kelayakan pengembangan E-Modul PPKn berbasis problem based learning pada pemahaman nilai-nilai Pancasila dan untuk mengetahui efektivitas penerapan E-Modul PPKn berbasis problem based learning terhadap peningkatan pemahaman siswa. Berdasarkan penelitian yang dilakukan peneliti tentang pengembangan E-Modul, diperoleh hasil bahwa E-Modul layak digunakan dalam pembelajaran dengan tingkat kelayakan yang didapat dari ahli media sebesar 95%, ahli materi sebesar 92,5%, uji coba siswa perseorangan sebesar 89,1%, uji coba kelompok kecil sebesar 83%, dan uji lapangan sebesar 86,5%. Analisis data dari hasil pre-test dan post-test siswa menunjukkan bahwa terdapat perbedaan hasil rata-rata antara pre-test sebesar 71,61% dan post-test sebesar 83,39%, sehingga dapat dikatakan bahwa E-Modul PPKn berbasis problem based learning efektif digunakan dalam pembelajaran.